The Subject(s) of Human Rights : Crises, Violations, and Asian/American Critique - Cathy J. Schlund-Vials; Guy Beauregard; Hsiu-chuan Lee (Temple University Press, 2020)
Human rights violations have always been part of Asian American studies. From Chinese immigration restrictions, the incarceration of Japanese Americans, yellow peril characterizations, and recent acts of deportation and Islamophobia, Asian Americans have consistently functioned as subordinated “subjects” of human rights violations. The Subject(s) of Human Rights brings together scholars from North America and Asia to recalibrate these human rights concerns from both sides of the Pacific. The essays in this collection provide a sharper understanding of how Asian/Americans have been subjected to human rights violations, how they act as subjects of history and agents of change, and how they produce knowledge around such subjects. The editors of and contributors to The Subject(s) of Human Rights examine refugee narratives, human trafficking, and citizenship issues in twentieth- and twenty-first century literature. These themes further refract issues of American war-making, settler colonialism, military occupation, collateral damage, and displacement that relocate the imagined geographies of Asian America from the periphery to the center of human rights critique.